2002
DOI: 10.1097/00005537-200209000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Facial Verrucae With the Pulsed Dye Laser

Abstract: Pulsed dye laser therapy is highly effective and safe therapy for facial verrucae. This method appears to selectively destroy warts without damaging surrounding skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 12 publications
2
38
1
Order By: Relevance
“…Two additional series of PDL for recalcitrant warts in adults and children noted clearance rates of 63% to 89% (18,19). Vargas et al (20) reported good cosmetic results for PDL treatment of 12 adults with facial warts who all had complete clearing without scarring after a maximum of three sessions.…”
Section: Phototherapies Lasermentioning
confidence: 99%
“…Two additional series of PDL for recalcitrant warts in adults and children noted clearance rates of 63% to 89% (18,19). Vargas et al (20) reported good cosmetic results for PDL treatment of 12 adults with facial warts who all had complete clearing without scarring after a maximum of three sessions.…”
Section: Phototherapies Lasermentioning
confidence: 99%
“…114 It produces less pain and scarring than with CO2 laser treatment and has been used for facial warts and perianal warts in children. 20,138,139 Pulse dye laser has been reported to result in complete remission in 48% to 95% of cases. 102,137,[140][141][142][143][144][145][146][147] One study found no statistically significant difference among cure rates between pulsed dye laser (66%) compared to conventional cryotherapy or cantharidin therapy (70%).…”
Section: Neodymium:yag (Nd:yag) Lasermentioning
confidence: 99%
“…The pulsed-dye laser at 585 nm has been used successfully to treat vascular malformation of the skin [22]. This wavelength is highly absorbed by hemoglobin and poorly absorbed by other tissue, allowing selective photocoagulation of submucosal blood vessels.…”
Section: Pulsed-dye Lasermentioning
confidence: 99%